Massive Cervicothoracic Subcutaneous Emphysema and Pneumomediastinum Developing during a Dental Hygiene Procedure - Gabriele Bocchialini; Serena Ambrosi; Andrea Castellani (Case Reports in Dentistry)
Subcutaneous emphysema is rare during or after dental procedures (usually extractions). Here, we describe the case of a 65-year-old woman who developed massive cervicothoracic subcutaneous emphysema and pneumomediastinum during a dental hygiene procedure employing an artificial airflow. She was diagnosed based on clinical manifestations and computed tomography (CT). CT revealed massive subcutaneous emphysema extending from the superior left eyelid to the diaphragm. We describe the clinical and radiological characteristics of this rare case.